THE ROLE OF FINANCIAL COMPENSATION IN ENHANCING MOTIVATION AND PERFORMANCE OF CONTRACT EMPLOYEES AT PT UNILEVER TBK - Siti Masruroh (CV Pena Jaya Pers, 2024)
arrangement. Giving suitable recompense is one such tactic. The purpose of this study is to: 1) investigate the implementation of financial compensation from the viewpoint of contract workers at PT Unilever Indonesia Tbk (2) evaluate the performance of contract workers at PT Unilever Indonesia Tbk; and 3) examine the connection between contract workers' performance and monetary pay at PT Unilever Indonesia Tbk. This study uses Pearson Product Moment correlation analysis using both primary and secondary data.The results, which are based on how employees see monetary remuneration and contract employee performance, show that both elements meet their expectations. Financial pay and contract employee performance have a high and positive link, as indicated by the correlation coefficient of 0.813.This suggests that financial compensation plays a significant role in enhancing the performance of contract employees at Unilever Indonesia Tbk.